Investigation on CO(2) laser irradiation inducing glass strip peeling for microchannel formation - Wang, Z. K. (American Institute of Physics, 2012)
The study investigates the use of CO(2) laser to induce glass strip peeling off to form microchannels on soda lime gass substrate. The strip peeling exhibits a strong dependence on the energy deposition rate on the glass surface. In spite of the vast difference in the combination of laser power and scanning speed, when the ratio of the two makes the energy deposition rate in the range 3.0-6.0 J/(cm(2) s), the temperature rising inside glass will be above the strain point and reach the softening region of the glass. As a result, glass strip peeling is able to occur and form microchannels with dimensions of 20-40 μm in depth and 200-280 μm in width on the glass surface. Beyond this range, higher energy depsotion rate would lead to surface melting associated with solidification cracks and lower energy deposition rate causes the generation of fragment cracks.